The nurse's secret - Skenandore, Amanda (New York, NY : Kensington Publishing Corp., 2022)
In 1880s New York, on the run for a murder she didn't commit, grifter Una Kelly takes refuge in Bellevue Hospital nursing school where she slowly gains friendship and self-respect until she is forced to choose between her instinct for self-preservation and exposing her identity in order to save others.
Includes reading group guide.
Includes bibliographical references (pages 354-355).
Keywords: Bellevue Hospital. -- Training School for Nurses -- History -- Fiction; Swindlers and swindling -- Fiction; Secrecy -- Fiction; Nursing -- Study and teaching -- New York (State) -- New York -- History -- Fiction; New York (N.Y.) -- Fiction; Historical fiction; Novels